2012
DOI: 10.1002/ange.201108706
|View full text |Cite
|
Sign up to set email alerts
|

Direct Catalytic Conversion of Methane to Methanol in an Aqueous Medium by using Copper‐Promoted Fe‐ZSM‐5

Abstract: Ein Eisen‐Kupfer‐Zeolith (Fe‐Cu‐ZSM‐5) katalysiert die selektive Oxidation von Methan zu Methanol mit wässrigem Wasserstoffperoxid. Das Eisen aktiviert die Kohlenstoff‐Wasserstoff‐Bindung, während das Kupfer dafür sorgt, dass Methanol als Hauptprodukt gebildet wird. Der Katalysator ist stabil und wiederverwendbar und aktiviert Methan mit >90 % Selektivität und 10 % Umsatz in einem geschlossenen Katalysezyklus (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 36 publications
8
89
1
6
Order By: Relevance
“…0.5 M and there was no requirement for a PPh3 additive. In line with analogous studies of the ZSM-5 catalysed oxidation of methane within the same group [98], the catalytic conversion of both ethane and H2O2 was attributed to extraframework iron sites. Indeed, whilst H-ZSM-5 (30) showed a rate of 2.8 molethane converted•kgcat −1 •h −1 , post synthesis deposition of 1.1 wt % Fe increased the rate to 47.1 molethane converted•kgcat −1 •h −1 under the same conditions [7].…”
Section: C2h6 + 4•ohsupporting
confidence: 77%
“…0.5 M and there was no requirement for a PPh3 additive. In line with analogous studies of the ZSM-5 catalysed oxidation of methane within the same group [98], the catalytic conversion of both ethane and H2O2 was attributed to extraframework iron sites. Indeed, whilst H-ZSM-5 (30) showed a rate of 2.8 molethane converted•kgcat −1 •h −1 , post synthesis deposition of 1.1 wt % Fe increased the rate to 47.1 molethane converted•kgcat −1 •h −1 under the same conditions [7].…”
Section: C2h6 + 4•ohsupporting
confidence: 77%
“…Such homogeneous processes have been extensively reviewed by Periana et al and Shilov et al [22,23] and heterogenised by Schüth and co-workers [24,25]. A number of homogeneously [26][27][28] and heterogeneously [29][30][31][32] catalysed aqueous processes for the direct oxidation of methane with H 2 O 2 have recently been reported. These benefit from the clean decomposition of the oxidant to H 2 O as an environmentally benign byproduct.…”
Section: Introductionmentioning
confidence: 95%
“…It has previously been reported that ZSM-5 materials containing trace amounts of iron (as dimeric -oxo-hydroxo iron species) can catalyse the direct conversion of methane and ethane to oxygenated products, utilising hydrogen peroxide as the oxidant [31,32,[38][39][40]. The oxidation of methane to methanol was shown to proceed via formation of methylhydroperoxide (CH 3 OOH), and deep oxidation to formic acid and CO 2 was observed [31].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Even the oxidation power of artificial Fenton and photoFenton systems is known to be high enough to hydroxylate aliphatic C-H bonds, inclusing CH 4 hydroxylation to methanol (Gopakumar et al, 2011;Hammond et al, 2012;Yoshizawa et al, 2000).…”
Section: Oxidation Of Organic Aerosol Particles Containing Black and mentioning
confidence: 99%